The Contributions of Youth Organisations to the Growth of Christ Apostolic Church in Southwestern Nigeria, 1943-2013 (2015)
Christ Apostolic Church (CAC), an African indigenous church, has various youth organisations, which have contributed significantly to the growth of the church. Previous studies on CAC have focused on the contributions of the founding fathers, as well as on men and women‟s associations with little attention paid to those of youth organisations. This study, therefore, examined youth organisations in the history of CAC in Southwestern Nigeria from 1943 to 2013 with a view to assessing their contributions to the growth of the church through church planting, promotion of formal education, leadership and career development. The study adopted Matthew Seebach‟s theory of youth participation. The Light of the World Society (LOWS), CAC Students‟ Association (CACSA) and CAC Youth Fellowship (CACYOF) were purposively selected being the most prominent youth groups in CAC. A questionnaire was used to elicit information from 542 (355 males and 187 females) purposively selected members of CAC in Abeokuta, Ado Ekiti, Akure, Ibadan, Lagos and Osogbo. In-depth interviews were conducted with 19 elderly pastors, 25 youth pastors and 12 youth leaders purposively selected from the Church. Church records were also consulted. Data were subjected to historical analysis and descriptive statistics. The LOWS planted 25 churches between 1966 and 1992 thereby increasing membership from 87,077 to 1,059,438. The CACSA planted 70 churches, leading to membership growth from 1,059,438 in 1992 to 4,707,438 in 2013. During the same period, CACYOF established 241 English-speaking assemblies resulting in the membership increase of 941,487 in 2013. Between 1971 and 2013, CACSA established 29 campus fellowship centres while CACYOF established 31 between 1992 and 2013. The CACYOF contributed to leadership development by initiating an annual Leadership Training Programme in 2002. This has produced many leaders for CAC. On career development, CACYOF organised seven empowerment seminars targeted at teaching vocational skills and creating job opportunities for youths in 11 centres between 2010 and 2013. In advancing infrastructural development, CACSA established a primary school, two secondary schools and a theological college in Osogbo between 1999 and 2009 while CACYOF introduced Information Communication Technology to the operations of CAC in Lagos, Ekiti, Ogun, Ondo, Osun and Oyo States from 2003 to 2013. A total of 93.5% respondents agreed that youth organisations contributed to the infrastructural growth of the church. Youth organisations have contributed to the growth of Christ Apostolic Church in southwestern, Nigeria. Therefore, youth organisations should be recognised in the growth and development of the church